1995
DOI: 10.1063/1.359718
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence characterization of InGaP/GaAs heterostructures grown by metalorganic chemical vapor deposition

Abstract: Growth conditions of metalorganic chemical vapor deposition have been investigated for the purpose of obtaining abrupt InGaP/GaAs interfaces. Photoluminescence (PL) spectra of InGaP/GaAs quantum wells (QWs) are used to characterize these interfaces. The conventional gas switching sequence, i.e., simultaneously switching on group-III and -V gases, is found to provide only a broad peak at wavelengths longer than those of near-band-edge emissions from GaAs in the PL spectrum of the InGaP/GaAs QW. PL studies using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…The high-energy peak around 1.43 eV comes from GaAs and the low-energy peak around 1.38 eV comes from an ''unintentional'' InGaAsP interfacial layer. 2,4,8 We note that the low-energy peak dominates the spectrum, indicating that most of the carriers created by the external excitation are localized and recombine in the interface regions. The growth of sample 1b is quite similar to that of sample 1a except that half the AsH 3 flow rate is used to passivate the GaAs surface during the interruption.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The high-energy peak around 1.43 eV comes from GaAs and the low-energy peak around 1.38 eV comes from an ''unintentional'' InGaAsP interfacial layer. 2,4,8 We note that the low-energy peak dominates the spectrum, indicating that most of the carriers created by the external excitation are localized and recombine in the interface regions. The growth of sample 1b is quite similar to that of sample 1a except that half the AsH 3 flow rate is used to passivate the GaAs surface during the interruption.…”
Section: Methodsmentioning
confidence: 97%
“…By growing an additional GaP or a large-bandgap AlGaAs layer, the formation of the low-bandgap interface layer can be effectively suppressed. 3,4,7 In this paper, we show that under optimized growth conditions, indium surface segregation plays an important role in the formation of a low-bandgap interface layer in the growth of InGaP/ GaAs heterostructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GaAs-on-GaInP interface is then found to be quasi abrupt, taking into account a probably small memory effect or interdiffusion of P in the well responsible for the formation of an GaAsP-like layer and resulting in the small blue shift of Samples A and B. Nevertheless, no segregation into the GaAs well was observed, otherwise PL lines should have been red shifted, and no 'Q-line' [7] was detected. On the contrary, the 9 ML thick well in Sample C, which was the inverse interface, emitted at a significantly lower energy than the calculated prediction (1633 meV instead of 1682 meV).…”
Section: Resultsmentioning
confidence: 86%
“…Formation of abrupt interfaces has been investigated by optimization of switching sequences [6] to avoid compositional intermixing and then localized strains around the heterointerfaces. Recently, Nittono et al [7] have reported in GaInP/GaAs quantum wells grown by MOCVD that the GaAs-on-GaInP interface is responsible for a broad peak at a longer wavelength than GaAs gap (called 'Q-line') and therefore the disappearance of the QW peak in the photoluminescence spectrum. They have also shown that the GaInP-on-GaAs interface is responsible for the lowering of the quantum-well energy transition by about 30-50 meV.…”
Section: Introductionmentioning
confidence: 98%